Customer segmentation approaches and hotel occupancy performance: A case study of 4 and 5 star hotels in Klang Valley / Noor Azmi Ahmad... [et al.] - Ahmad, Noor Azmi; Kamarudin, Syaquif Yasin; Abdul Aziz, Azdel; Bakhtiar, Mohd Faeez Saiful; Che Ahmat, Nur Hidayah (2011)
Yield Management (YM) has been described as a method that can help an organization to sell the right inventory, to the right customer, at the right timeNfor the right price. Application of YM strategies involves the hotel to practice market segmentation strategies in Malaysia has not been highlighted. Though in theory it may described strategies that can be practiced, this paper provide unforeseen glimpse of segmentation approaches practiced by hotel managers. This paper seeks to conceptualize the relationship of application of market segmentation strategy and occupancy performance by four (4) and five (5) star hotels in Klang Vallley. Data collected from 37 hotels in Klang Valley area shows positive insights in research issues. Through the data collections and analyses the outcomes show the current market segmentation practices. A relationship between hotel that practise market segmentation strategies and revenue management performance is proven. It also showed the segmentation strategies hotel practise to attract most contributing market. For the conclusion, Hotel that practice effective market segmentation will have higher occupancy performance compared to other hotel.